PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INTODUKTION DENGAN GOOGLE CLASSROOM DALAM MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS X RPL 1 SMK NEGERI 1 NEGARA TAHUN PELAJARAN 2020/2021 (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The purpose of this study was to determine whether there was a student response or the effect of the application of the problem-based instruction learning model in improving the physics learning achievement of class X RPL 1 students of SMK Negeri 1 Negara in the 2020/2021 school year. This type of research is classroom action research with distance learning using the Google Classroom application. The subjects of this study were students of class X RPL 1 SMK Negeri 1 Negara with a total of 36 students. The object of research on students' abilities in Dynamic Electricity. This research was conducted in class X RPL 1 SMK Negeri 1 Negara in the even semester of the 2020/2021 school year. This research uses test and observation methods. This research was conducted in two cycles and each cycle consisted of four stages, namely: planning the action, implementing the action, observing / evaluating, and reflecting. The results showed (1) there was an effect of the application of the Problem Based Instruction learning model, this was evident from the increase in the average value. -The average of students from cycle I to cycle II was 8.47% (2) Student response to physics lessons on the application of the Problem Based Instruction learning model in improving student achievement in class X RPL 1 SMK Negeri 1 Negara in the 2020/2021 school year is good. There is an increase in the average value of 13.95%.